MANAJEMEN PERENCANAAN BISNIS SYARIAH PADA E-COMMERCE - Efriza Pahlevi Wulandari; Muhammad Akbar; Nurfadilah Sindika Sari; Achmad Shidiq (Institut Agama Islam K.H. Sufyan Tsauri, 2024)
The large digital market in Indonesia has made startups mushroom in Indonesia. If this continues, online business competition will become increasingly tight and a mature business plan is needed to survive and compete with competitors. The application of sharia principles to online businesses and their planning has been studied for a long time, so it is not something new. However, sharia business planning has not been fully applied to online businesses. This study uses a descriptive analysis method through a literature review of journals and articles. Sharia business planning in online businesses must pay attention to maqashid sharia through the implementation of buying and selling transaction procedures, namely buyers register and sign in, buyers choose products, make purchases, make payments, sellers send products to buyers, and certain conditions such as returns and exchanges. The implementation of the transaction procedure for buying and selling must be in accordance with the principles of buying and selling in Islam which are carried out with elements of willingness with the existence of a contract, the benefits of the object and subject being transacted, justice with pricing and taking reasonable profits, not exploiting, being honest about the product information conveyed in detail, freedom from khiyar, avoiding elements that are prohibited in Islam, namely maisir, gharar, usury and haram, and sahih, namely the conditions and pillars of buying and selling on e-commerce are met.